Cobalt sulfide as photoelectrode of photoelectrochemical hydrogen generation from water - Rambey, Mustafid Amna; Khuzaimah Arifin,; Lorna Jeffery Minggu,; Mohammad Kassim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study aimed to synthesize and characterize cobalt sulfide deposited on FTO by hydrothermal method and investigate its photoelectrochemical (PEC) water splitting performance. Cobalt sulfide thin films were produced by annealing at two different temperatures, namely, 400 and 500 °C. X-ray diffraction (XRD) and Fourier transform Raman spectroscopy were used to characterize the phase structure. Scanning electron microscopy was used to observe the morphology. Ultraviolet-visible spectroscopy and linear sweep voltammetry analyses were used to determine the thinfilm band gap and evaluate the PEC water splitting performance, respectively. From the XRD and Raman analyses, all the samples produced consisted of mixed phases of Co3 S4 and Co9 S8 . However, each sample contained different percentage phases. The sample annealed at 400 °C contained more Co9 S8 , whereas that annealed at 500 °C contained comparable amounts of Co3 S4 and Co9 S8 . The morphologies of pre-annealed samples showed vertical flakes with diameters around 200-250 nm and flake thickness around 25-50 nm. When the temperature was increased from preannealing temperature to 400 and 500 °C, several flakes were destructed and formed spherical-like clusters. The Tauc plot from absorption analysis showed that the samples annealed at 400 and 500 °C produced similar band gaps at ~2.0 eV. The PEC performance analysis results show that annealing at 400 °C produced the highest photocurrent density of 10 µA/cm2 at a potential of -0.7 V.